TDPAC investigation on NH4 Hf2 F9 - Martínez, Jorge Alberto (1983)
Time-differential perturbed angular correlation (TDPAC) measurements in NH4Hf2F9 were performed between 15 and 580 K. The compound was found to be stable in the whole temperature range and no phase transitions were observed. Experimental results could be explained assuming two equally populated quadrupole interactions which suggest a neat inequivalence between the two sites occupied by the hafnium atoms in the molecule.